Literacy at play: an analysis of media literacy games used to foster media literacy competencies - Glas, René; van Vught, Jasper; Fluitsma, Timo; De La Hera, Teresa; Gómez-García, Salvador (Frontiers in Communication, 2023)
Digital media literacy is considered one of the key competencies to acquire in the 21st century. With games being recognized as having large potential to train and educate, a wide range of games focusing on media literacy related topics such as fake news games, digital privacy, personal media habits, and practical media skills have sprung up over the years. All claim to foster media literacy skills and competencies. This begs the question how these games generally frame and understand media literacy, what competencies and skills they actually focus on, and through which game design choices. This paper thus asks: how media literacy games are designed to foster digital information literacy? Taking the Dutch Media Literacy Competencies Model as a departure point, we answer this question using a thematic analysis of 100 media literacy games and formal analysis of a smaller heterogeneous sample consisting of 12 games. We present a series of key findings involving the prominent presence of certain topics and competencies in the dataset, as well as prevalent design choices, allowing for a discussion of the current landscape of literacy games and underlying competencies and future potential for development.